Students’ Perception on the Use of Role Play at English Education Department of Universitas Muhammadiyah Yogyakarta - Aprilia Puspawardhani (FPB I 15 UMY 024, 2015)
*24 Role play becomes one of the techniquesin speaking class. Despite the benefits provided in role play, students commonly faced some obstacles in the implementation of role play that some teachers implement in a speaking class. Thus, the researcher is interested to find out students’ perception on the use of role play in speaking class at English Education Department of Universitas Muhammadiyah Yogyakarta. The descriptive qualitative research was used as the research method. Six students of English Education Department batch 2011 who became respondents of this research were selected using snowball sampling. The data was obtained through semi-structured interview in Bahasa Indonesia. Member checking was done to get the validity of the interview data. Then the researcher analyzed the data using open, axial, and selective coding. The first finding was about the students’ perception on the implementation of role play in speaking classes at EED of UMY. The finding showed that experience of role play was implemented in the first and the seventh semesters in the subjects of listening and speaking for daily conversation, listening and speaking for formal setting and interpreting. The second finding was about students’ perception of the functions of role play in speaking class. There were eleven functions of role play perceived by the students namely learn to communicate and interact with others in daily context, enhance students’ engagement, improve students’ fluency, pronunciation, and readiness, improve students’ confidence, appreciate and praise each other, become creative to make xii scenario building, develop critical thinking, practice to speak, remember longer, avoid boredom, train facial expression. The third finding was about the students’ perception on the stages of role play in speaking class. There were six stages in the implementation of role play which were that students are given role or topic, students are grouped, students share and discuss ideas to make scenario, students make preparation; make and memorize the script and prepare costume, students are given time to show, and students are given time to consult. Then, the next finding of this research was about students’ perception on the significances of role play in speaking class. There were eleven significances of role play perceived by the respondents which were to communicate in daily life context, interact with others in different characters, communicate more effectively, improve students’ confidence, motivate to speak English, improve speaking skill, enhance vocabulary, become more expressive and creative, become more aware of new things, build team work, make learning more enjoyable and interesting. The last finding was about students’ perception on the challenges of role play in speaking class. There five challenges of role play commonly faced by students in speaking class. The challenges were team work problem consist of difficult to act different characters, lack of communication, lack of appreciation and minimum time management, lack of confidence, feeling shy and nervous, difficult to memorize and different proficiency level.